Rancang Bangun Alat Penakar Minyak Goreng Berbasis Mikrokontroler - Fiqri, Muhammad Al; Zulrian Aldio, Rieza; Yonatan, Yoel (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
One of the current technologies is the ability of a capable of running automatically is more beneficial for its users because it can be easy when doing work with more efficient, economical, and practical results. the design of a measuring device can be done with the aim of making it easier for humans to measure cooking oil and minimise the possibility of measuring errors with a tool that is more effective and uses high accuracy by utilising a microcontroller as a measuring device. by using a flow sensor Flow sensor is one of the microcontroller's external peripherals that functions to measure the flow rate. To drain the fluid in the need for a pump, in this study the pump used with specifications: Voltage: 220 V. Output Power: 125 Watt. Temperature. Maximum Total Height: 30 m. Push Height: 24 m. Suction Height: 9 m